ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN MENGGUNAKAN METODE HAZID, HIRA, FINE, DAN HAZOP PADA JIRAK WATERFLOOD PROJECT - Zahra Putri Wardana, (2023)
Basically, construction project activities are efforts to fulfill human needs. The construction process involves the use of heavy equipment, hazardous chemicals, and strenuous physical activities, so the construction industry is a sector that has a high level of work risk. This study aims to identify and analyze OHS (Occupational Health and Safety) risks using the Hazard Analysis method which consists of Hazard Identification (HAZID), Hazard Identification and Risk Assessment (HIRA), Fine, and Hazard Operability (HAZOP). Data collection techniques in this study were carried out through observation, interviews and questionnaires. Data processing techniques in this study were carried out by testing the validity and reliability tests. The data analysis technique in this study was carried out using the HAZID, HIRA, Fine, and HAZOP methods. The results obtained from this study are as many as 36 risks that have the possibility of work accidents at the Jirak Waterflood Project, in the HIRA method obtained for the Extreme (E) risk category as many as 5 risk items, in the Fine method for the Priority 1 risk category as many as 4 risk items, Priority 3 risk category with 1 risk item.